HLA alleles and haplotypes in Burmese (Myanmarese) and Karen in Thailand. Issue 3 (September 2015) - Kongmaroeng, C.; Romphruk, A.; Puapairoj, C.; Leelayuwat, C.; Kulski, J. K.; Inoko, H.; Dunn, D. S.; Romphruk, A. V.
Abstract This is the first report on human leukocyte antigen (HLA) allele and haplotype frequencies at three class I loci and two class II loci in unrelated healthy individuals from two ethnic groups, 170 Burmese and 200 Karen, originally from Burma (Myanmar), but sampled while residing in Thailand. Overall, the HLA allele and haplotype frequencies detected by polymerase chain reaction sequence‐specific primer (PCR‐SSP) at five loci (A, B, C, DRB1 and DRQB1) at low resolution showed distinct differences between the Burmese and Karen. In Burmese, five HLA‐B*15 haplotypes with different HLA‐A and HLA‐DR/DQ combinations were detected with three of these not previously reported in other Asian populations. The data are important in the fields of anthropology, transplantation and disease‐association studies.